Brothers and Sisters in India : A Study of Urban Adult Siblings - Ramu, G. N., 1937- (Book collections on Project MUSE., 2006)
The brothers and sisters investigated in this study, together demonstrate that the nature and function of kinship ties in India are undergoing striking changes - changes which may converge with similar patterns found in Western societies.